Features of the self-restoration of the oil-contaminated peat-bog soil – a field study - Chugunova Marina; Bakina Lyudmila; Gerasimov Alexander (BIO Web of Conferences, 2023)
The features of self-restoration processes of the oligotrophic peat-bog soil disturbed by crude oil pollution were studied. Soil contamination was carried out in field long-term experience. The key soil self-recovery indicators were: (1) the rate of carbon dioxide emission by the soil, which quantitatively characterizes the mineralization of petroleum hydrocarbons by microorganisms; (2) content of petroleum products. The microorganisms of the studied soil were characterized by low resistance to the toxic effects of oil: during the first three years of the experiment, the respiration of oil-contaminated soils was significantly lower than in pure soil. Restoration of microbial respiration to the control level and its further intensive growth occurred after 4-5 years of the experiment only in soils with low oil doses: 0.3 and 0.6 l m-2. In time, this coincided with the maximum rate of oil decomposition, which indicates the microbial nature of its utilization. The respiration of soil with oil high doses (1.8 and 3.0 l m-2) remained significantly lower than in pure soil throughout the entire experiment. At the same time, the amount of oil products in these samples markedly decreased. Oil degradation in these variants could occur due to the activity of anaerobic bacteria or abiotic processes.